Level of professional Burnout among family physicians in the Republic of Moldova and certain aspects regarding its contributing factors - Victoria CIORNEI; Adriana PALADI (One Health & Risk Management)
Introduction. Family medicine represents a key component of the healthcare system, a specialty characterized by fragmented work, high demands from patients/families/communities, and often conflicting interactions, all of which are conditions that predict stress and the onset of burnout. The aim of this study was to assess the degree to which family physicians in the Republic of Moldova are affected by professional burnout, as well as to identify its determining factors.